IMPLEMENTASI PROGRAM TAHFIZ HADIS DALAM MEMBENTUK KARAKTER SISWA MA ANNIDA AL ISLAMY JAKARTA BARAT - Siti Shopiyah; Dian Afifah (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This study is motivated by the large number of Islamic-based schools that havetahfizAl-Quran programs, but few schools have tahfiz hadis programs. As it is known that the Qur'an and hadith are the source of Islamic teachings. One of the schools that has a hadithtahfizprogram is MA Annida Al Islamy West Jakarta. Therefore, the author is interested in knowing the character that is formed in students through the tahfiz hadith program. The purpose of this study is to find out the implementation of the hadith memorization program at MA Annida Al Islamy West Jakarta and to find out the characters formed from the implementation of the hadith memorization program at MA Annida West Jakarta. The research method used in this research is descriptive qualitative. The data collection techniques used are observation, interviews, and documentation. The results of this study are (1) Implementation of the hadith memorization program on Wednesdays and Fridays at 14.00-16.00 WIB, sometimes the activity schedule changes at any time according to the situation. The activity is guided by the supervising teacher which includes: depositing memorization, testing the memorization of past hadith, and improving the intonation of the hadith recitation. On Fridays, students attend hadith lessons taught by the hadith tahfiz instructor, which include: reciting hadith in accordance with makharijul letters, intonation, fashohah, waqaf, and ibtida. Since the hadith is dialogic, these things will affect the person who hears and understands it. Next is to provide tarjamah, mufrodat, and fawaid or the essence of the hadith. (2) The implementation of thetahfizhadis program can shape several student characters, namely: obedient character, honest character, disciplined character, responsible character, and polite character.